Strategies for the compensation of specimen-induced spherical aberration in confocal microscopy of skin. - Booth, M; Wilson, T (2000)
We consider various strategies for confocal imaging of human skin which seek to reduce the effects of the specimen-induced aberrations. We calculate the spherical aberration introduced by the stratified structure of skin and show how the confocal signal is affected when attempting to image at various depths within the dermis. Using simple methods it is shown how images might be improved by compensating for the induced aberration. The methods include the use of an iris to reduce the pupil area, changing the refractive index of the immersion medium and using a lens with variable coverglass correction.